Antifungal efficacy of phytoconstituents of Medicago sativa against Rhizoctonia solani - Anwaar, Amina; Jabeen, Khajista; Iqbal, Sumera; Javad, Sumera (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2021)
This research was carried out to study the antifungal properties of Medicago sativa L. against phytopathogenic fungus Rhizoctonia solani J.G. Kühn. Methanolic extract of M. sativa was estimated in vitro against the R. solani. M. sativa methanolic extract was found to be highly efficient at the concentration of 5% as it reduced 74% test fungus biomass. Test plant was further partitioned by five organic fractions namely, n-butanol, chloroform, ethyl acetate, acetone and n-hexane. These isolated fractions and synthetic fungicide control group were evaluated in vitro against R. solani. Results showed that ethyl acetate fraction and fungicide were most effectively to repress the growth of R. solani up to 61-67%. This ethyl acetate fraction was further carried out for analysis of GC-MS and nine bioactive agents were found. The most copious compounds were phytol (RT: 20.84), 1,2,3-Propanetriol, monoacetate (RT: 12.47), Z,Z-3, 15-Octadecadien-1-olacetate (RT: 21.75), Hexadecanoic acid, ethyl ester (RT: 19.72) and Benzene, nitro- (RT: 10.20). The present study can be concluded that M. sativa possesses antifungal constituents against R. solani.